Práticas educativas digitais: uma cultura participativa em formação - Martins, Cibelle Amorim (2015)
This research had been effected in the contemporary historical moment characterized by the cyberculture enlargement, which is increasingly a fine line between the spaces geographically located and those produced in the world wide network, the Internet. This scenery has provided favorable conditions for the development of a participatory culture. The challenge posed to school and their educational practices is dealing with this new dynamic by which the individual has broad access to information. It raised the hypothesis that there is a participatory culture in formation, especially outside schools, in the virtual spaces. The thesis is that this participatory culture fills the meaning of digital educational practices. The central question from which this research had been developed led us to investigate what facilitated/ hindered the formation of a participatory culture both within and outside the school in the new spaces structured in sociodigitals networks. For all that, the main purpose of this study was to construct a concept of digital educational practices, filling with floating signifier "participatory culture", identifying its origin, nature and relationship to the educational phenomena. In times indicating paradigmatic changes in education, this research was conducted in a qualitative approach, with contribution in virtual ethnography. Part of the empirical research had been conducted in Portugal, which open interviews took place with those involved in formal educational practices. Also occurred photographic records of the school apace. A second moment of the study had been developed in Brazil through online questionnaires for the school counselors and analysis of a unique virtual community for those people. It obtained multimodal data represented in photographs, narratives and charts that shows the little impact of cultural changes in educational paradigms of the school field that had been studied. It highlights, on the other hand, the important role of schools in building a culture of participation, where all the actors involved in the educational practices need to exercise their citizenship in a more integrated, cohesive, decentralized and diffuse.